2005
DOI: 10.1098/rsbl.2005.0354
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals Holocene loss of genetic diversity in a South American rodent

Abstract: Understanding how animal populations have evolved in response to palaeoenvironmental conditions is essential for predicting the impact of future environmental change on current biodiversity. Analyses of ancient DNA provide a unique opportunity to track population responses to prehistoric environments. We explored the effects of palaeoenvironmental change on the colonial tuco-tuco ( Ctenomys sociabilis ), a highly endemic species of Patagonian rodent that is currently listed as threatene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 16 publications
8
86
1
1
Order By: Relevance
“…However, this reasoning by analogy can be inappropriate if the groups compared have differing demographic and phylogenetic histories. Analyses of historical specimens can provide information on historical levels of genetic diversity (e.g., Bouzat et al, 1998;Hadly et al, 1998;Groombridge et al, 2000;Matocq and Villablanca, 2001;Larson et al, 2002;Paxinos et al, 2002;Nyström et al, 2006); responses to climate change (e.g., Orlando et al, 2002;Barnosky et al, 2003;Hadly et al, 2003;Shapiro et al, 2004;Chan et al, 2005); systematics (Goldstein and Desalle, 2003;Krause et al, 2006;Poulakakis et al, 2006); rates of evolution (e.g., Lambert et al, 2002); bottleneck events (e.g., Hadly et al, 2003); and historical population dynamics (e.g., Leonard et al, 2000;Pertoldi et al, 2001;Barnes et al, 2002;Orlando et al, 2002;Shapiro et al, 2004). Many of these analyses have potential application in conservation genetics for species management, the evaluation of species recovery, and even the projection and prediction of biological responses to future environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this reasoning by analogy can be inappropriate if the groups compared have differing demographic and phylogenetic histories. Analyses of historical specimens can provide information on historical levels of genetic diversity (e.g., Bouzat et al, 1998;Hadly et al, 1998;Groombridge et al, 2000;Matocq and Villablanca, 2001;Larson et al, 2002;Paxinos et al, 2002;Nyström et al, 2006); responses to climate change (e.g., Orlando et al, 2002;Barnosky et al, 2003;Hadly et al, 2003;Shapiro et al, 2004;Chan et al, 2005); systematics (Goldstein and Desalle, 2003;Krause et al, 2006;Poulakakis et al, 2006); rates of evolution (e.g., Lambert et al, 2002); bottleneck events (e.g., Hadly et al, 2003); and historical population dynamics (e.g., Leonard et al, 2000;Pertoldi et al, 2001;Barnes et al, 2002;Orlando et al, 2002;Shapiro et al, 2004). Many of these analyses have potential application in conservation genetics for species management, the evaluation of species recovery, and even the projection and prediction of biological responses to future environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Further inference can be gained through tracking the loss of diversity over time (e.g. Chan et al 2005). At the same time, it is important to understand the potential impact of environmental change on the connectivity and dynamics of larger populations.…”
Section: Bottlenecks and Foundersmentioning
confidence: 99%
“…For example, endangered species often demonstrate reduced genetic variation when compared to non-endangered relatives (Frankham 1995), and such a pattern is usually interpreted to be the result of recent, known bottlenecks in population size (Frankham et al 2002;Avise 2004). But recent studies have shown that, in at least some cases, low genetic diversity may be due to prehistoric events rather than modern-day anthropogenic disturbances (Chan et al 2005;Paxinos et al 2002). Many studies of endangered species also examine the level of genetic differentiation between fragmented, remnant populations to determine whether gene flow is being limited (Frankham et al 2002).…”
Section: Introductionmentioning
confidence: 99%